2020
DOI: 10.3390/pharmaceutics12111067
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lidocaine-Loaded Dissolving Microneedle for Rapid and Efficient Local Anesthesia

Abstract: Lidocaine is a local anesthetic agent used in the form of injection and topical cream. However, these formulation types have limitations of being either painful or slow-acting, thereby hindering effective and complete clinical performance of lidocaine. Dissolving microneedles (DMNs) are used to overcome these limitations owing to their fast onset time and minimally invasive administration methods. Using hyaluronic acid and lidocaine to produce the drug solution, a lidocaine HCl encapsulated DMN (Li-DMN) was fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…This includes sodium alginate and poly(vinyl) alcohol hydrogels for enhanced skin delivery of quercetin (a natural polyphenolic flavonoid commonly found in fruits and vegetables and known for anti-inflammatory and antioxidant effects) as an example system that could be considered as an option for the treatment of skin ageing and inflammation [ 8 ]. Microneedle-based systems for administration of local anaesthesia (lidocaine) are reported by Yang et al [ 9 ], confirming the delivery of clinically-relevant levels of lidocaine and a fast onset time. Akrawi and colleagues [ 10 ] detail the generation of a chitosan-coated nanoemulsion system for delivery of naringenin (a natural flavonoid known to possess antioxidant, antimicrobial and anti-inflammatory characteristics) as a potential platform to accelerate wound healing.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…This includes sodium alginate and poly(vinyl) alcohol hydrogels for enhanced skin delivery of quercetin (a natural polyphenolic flavonoid commonly found in fruits and vegetables and known for anti-inflammatory and antioxidant effects) as an example system that could be considered as an option for the treatment of skin ageing and inflammation [ 8 ]. Microneedle-based systems for administration of local anaesthesia (lidocaine) are reported by Yang et al [ 9 ], confirming the delivery of clinically-relevant levels of lidocaine and a fast onset time. Akrawi and colleagues [ 10 ] detail the generation of a chitosan-coated nanoemulsion system for delivery of naringenin (a natural flavonoid known to possess antioxidant, antimicrobial and anti-inflammatory characteristics) as a potential platform to accelerate wound healing.…”
mentioning
confidence: 69%
“…Non-invasive drug delivery research is an active, rich and multidisciplinary research area and this Special Issue aims to present the current state of the art in the field. The contributions in this Special Issue address drug delivery systems for administration through the oral route [ 1 , 2 , 3 , 4 ], respiratory administration [ 5 , 6 ], nose-to-brain delivery [ 7 ] and via the skin [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Furthermore, a broad range of drug delivery systems and therapeutics (both small drug molecules and biologics) for non-invasive delivery were investigated and discussed, including nanosystems such as silica nanoparticles [ 15 ].…”
mentioning
confidence: 99%
“…Many previous studies have confirmed that dissolving MNs could be utilized as an efficient tool for improving the penetration rate and delivery efficiency of an encapsulated drug [ 35 , 72 , 73 ]. In this experiment, full thickness isolated porcine skin was used as a drug permeable membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the manufacture of dissolving MNs is comparatively easier than other types of MNs. Dissolving MNs have been developed to deliver a series of drugs, including small molecules and macromolecules, such as DNA and protein [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, ENL formulations can be sprayed onto the skin upon MN pretreatment. Another comparable approach is the development of LidH-containing dissolvable MNs, which combine the steps of skin treatment and LidH delivery into one step to achieve the rapid onset of local anesthesia, as reported by Yang et al [ 35 ]. Both the methods using the MN pretreatment plus spray and dissolvable MNs are competitive and worthy of further investigation and optimization regarding the safety, efficacy, patient compliance, and manufacture costs.…”
Section: Discussionmentioning
confidence: 99%